Pemerolehan Bahasa Anak Periode Linguistik - Rezeki, Tri Indah; Sagala, Rakhmat Wahyudin (Universitas Mathla'ul Anwar Banten, 2019)
Language acquisition of human being was started when children learned to talk. Children who are able to speak as well as adults can be called children on linguistic period namely language acquisition period from 1 to 5 years old. Specifically, this study aims to describe language acquisition of children on linguistic period. The subject of this study was children aged 3 years old and 5 years old. Research methodology applied qualitative descriptive research by Miles and Huberman. The researchers did some activities in this study such as: (1) collected the data of language acquisition from children in linguistic period; (2) obtained the data through observation, interview and documentation; (3) analyzed the data based on the theory of children’s language acquisition period and factors which affect language acquisition. Based on the data, it can concluded that children aged 3 years old and 5 years old had language development period namely two-word speech stage, word inflection, question and refuse sentences, rare and complex stages of construction. Meanwhile, factors which affect children language acquisition aged 3 years and 5 years old were heredity include intelligence and personality factors, social background factors include family relationships, social status and surrounding environment.